1999
DOI: 10.1006/dbio.1999.9332
|View full text |Cite
|
Sign up to set email alerts
|

A Paraxial Exclusion Zone Creates Patterned Cranial Neural Crest Cell Outgrowth Adjacent to Rhombomeres 3 and 5

Abstract: Cranial neural crest cell migration is patterned, with neural crest cell-free zones adjacent to rhombomere (R) 3 and R5. These zones have been suggested to result from death of premigratory neural crest cells via upregulation of BMP-4 and Msx-2 in R3 and R5, consequent to R2-, R4-, and R6-derived signals. We reinvestigated this model and found that cell death detected by acridine orange staining in avian embryos varied widely numerically and in pattern, but with a tendency for an elevated zone centered at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 38 publications
3
56
0
1
Order By: Relevance
“…One of the main consequences of this inductive interaction is to promote the expression of the signalling molecules in the crest primordia of rhombomeres 3 and 5, which in turn acts to sponsor the apoptotic elimination of these cells (Graham et al, 1994). In vitro application of Bmp-4 can also promote crest depletion of rhombomeres 2 and 6, which correlates with the finding that much of the hindbrain neural crest expresses the necessary receptors and intracellular effectors to respond to this factor (Farlie et al, 1999;Smith and Graham, 2001). Bmp-4 will not induce, however, cell death in rhombomere 4 neural crest, which corresponds with the finding that these crest cells express the Bmp-4 antagonist Noggin in addition to the Bmp receptors and intracellular transducers (Smith and Graham, 2001).…”
Section: Segregation Of the Cranial Crest Streamssupporting
confidence: 53%
See 1 more Smart Citation
“…One of the main consequences of this inductive interaction is to promote the expression of the signalling molecules in the crest primordia of rhombomeres 3 and 5, which in turn acts to sponsor the apoptotic elimination of these cells (Graham et al, 1994). In vitro application of Bmp-4 can also promote crest depletion of rhombomeres 2 and 6, which correlates with the finding that much of the hindbrain neural crest expresses the necessary receptors and intracellular effectors to respond to this factor (Farlie et al, 1999;Smith and Graham, 2001). Bmp-4 will not induce, however, cell death in rhombomere 4 neural crest, which corresponds with the finding that these crest cells express the Bmp-4 antagonist Noggin in addition to the Bmp receptors and intracellular transducers (Smith and Graham, 2001).…”
Section: Segregation Of the Cranial Crest Streamssupporting
confidence: 53%
“…This effect could be due to the expression in both rhombomeres 3 and 5 of Sema3A, a molecule which is known to inhibit neural crest migration (Eickholt et al, 1999). Similarly, it has been suggested that the mesenchyme opposite these two segments is inhibitory to neural crest migration (Farlie et al, 1999) and that this finding is due to the function of ErbB4 in the hindbrain (Golding et al, 2000). These studies help explain why the few crest cells generated by rhombomeres 3 and 5 do not move laterally from these rhombomeres but migrate anterior and posterior.…”
Section: Segregation Of the Cranial Crest Streamsmentioning
confidence: 82%
“…At hindbrain levels, neural crest cell migration is segmented into three distinct streams adjacent to rhombomere 2 (r2), r4 and r6, with no neural crest cells apparent adjacent to r3 and r5. Cranial neural crest streams form from a combination of reduced neural crest production from r3 and r5 (reviewed in Kulesa et al, 2004) and an environment inhibitory to neural crest migration in the adjacent mesenchyme (Farlie et al, 1999;Trainor et al, 2002;Kulesa et al, 2004). Those cells originating in r3 and r5 deviate rostrally or caudally and fail to enter the adjacent preotic mesoderm or otic vesicle region (Sechrist et al, 1993;Kulesa and Fraser, 2000;Trainor et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that environmental influences adjacent to r3 and r5 may be critical in controlling the pathways of hindbrain neural crest migration (Farlie et al, 1999) and distinct mechanisms may be used by different species to pattern these events. For instance, unlike chick and mouse, cranial neural crest cells in zebrafish arise from the lateral portion of the neural keel, which remains for a limited period as a coherent mass adjacent to the neural keel extending from the optic cup caudally to the otocyst.…”
Section: How Are Neural Crest-free Zones Generated?mentioning
confidence: 93%
“…The segmental organization of the hindbrain is particularly important in patterning the neural crest cell migration pathways. Cranial neural crest cells in all vertebrates generally migrate in discrete segregated streams often separated by clear neural crest-free zones (Farlie et al, 1999). Over the past decade, there has been some debate concerning how the distinct migratory neural crest cell streams are established and in particular the importance of apoptotic cell death (Graham et al, 1993(Graham et al, , 1994Trainor et al, 2002).…”
Section: Introductionmentioning
confidence: 99%